IMPLEMENTASI AKUNTANSI SYARIAH MUDHARABAH MENURUT STANDAR AKUNTANSI KEUANGAN PADA PT. BANK MUAMALAT INDONESIA CABANG MAKASSAR - Ibrahim Ibrahim (AkMen JURNAL ILMIAH, 2013)
This study aimed to determine whether the accounting is in conformity with the Islamic mudaraba Accepted Accounting Principles (GAAP) in the PT. Bank Muamalat Indonesia Makassar Branch. The analysis method used is descriptive comparative analysis method, ie by comparing the accounting treatment for the results conducted by Bank Muamalat Indonesia Cab. Makassar with the accounting treatment under Statement of Financial Accounting Standards (IFRSs). From the analysis it can be concluded the discussion: First, for financing the accounting treatment in accordance with Financial Accounting Standards generally recognized where cash financing and measurement basis using historical cost. Second, for the accounting treatment of revenue sharing by PT. Bank Muamalat Indonesia is not in accordance with GAAP especially regarding recognition method in which the Bank Muamalat recognized on cash basis while the SAK stated that income and interest expense recognized on accrual basis. Third, for the accounting treatment of revenue in terms of fees and commissions is not appropriate because the SAK Muamalat fee and commission income is recognized immediately as revenue in all periods, while in commission income and fees SAK indirectly acknowledged its entirety as revenue in the period but estimated according the credit period. This more clearly illustrates how commissions and fees revenue in each period.